Plant growth-promoting rhizobacteria enhanced induced systemic resistance of tomato against Botrytis cinerea phytopathogen - Mazuecos-Aguilera, Ismael; Anta-Fernández, Francisco; Crespo-Barreiro, Andrea; Martínez-Quesada, Alejandro; Lombana-Larrea, Luis; González-Andrés, Fernando (Frontiers in Plant Science, 2025)
IntroductionBotrytis cinerea is one of the pathogenic fungi causing major problems worldwide in crops such as tomato. Some Plant Growth-Promoting Rhizobacteria (PGPR) can activate induced systemic resistance (ISR) pathways in crops, reducing the need for antifungals.MethodsThree strains belonging to the species Peribacillus frigoritolerans (CD_FICOS_02), Pseudomonas canadensis (CD_FICOS_03), and Azotobacter chroococcum (CD_FICOS_04), which exhibit outstanding PGPR properties, were evaluated for their ability to protect tomato plants against B. cinerea infection by ISR via soil inoculation.ResultsThe strains CD_FICOS_02 and CD_FICOS_03 reduced B. cinerea incidence and plant oxidative stress. The first strain mainly increased the expression of genes related to the salicylic acid pathway, while the second increased the expression of genes related to the jasmonic acid/ethylene hormonal pathway, indicating preferential ISR activation by each of these pathways. In addition, CD_FICOS_03 was able to increase the root and aerial biomass production of infected plants compared to the control. Interestingly, although the strain CD_FICOS_04 did not reduce the damage caused by B. cinerea, it increased the biomass of infected plants.DiscussionOur results suggest that the best strategy for biocontrol of B. cinerea is to combine the ability to promote plant growth with the ability to induce systemic resistance, as demonstrated by strains P. frigoritolerans CD_FICOS_02 and P. canadensis CD_FICOS_03.